The Influence of Learning Motivation and Numeracy on High School Students - Lestari, Ayu; Septian, Ari; Inayah, Sarah (Universitas Suryakancana, 2024)
This research aims to analyze the influence of learning motivation on numeracy in trigonometry material. The method used is quantitative. The subjects in this research were 54 Pasundan 1 Cianjur High School students who were given four numeracy test questions and 20 learning motivation questionnaire statements. The instruments used are descriptive test questions and non-test questions in the form of questionnaires. Data analysis techniques use normality tests, homoscedasticity tests, linearity tests and simple linear regression tests. Based on the research results, a conclusion was obtained: The achievement of the highest percentage of learning motivation is interpreting the results of the analysis to predict and make decisions, including good criteria. The lowest percentage is that there is a conducive environment with sufficient criteria. The achievement of the highest percentage of student numeracy was interpreting the results of the analysis to predict and make decisions, including good criteria. The lowest percentage is being able to analyze information displayed in various forms (graphs, tables, charts, diagrams and so on), with sufficient criteria. There is an influence of learning motivation on high school students' numeracy.